Alkali grinding activation-based analcime as well as preparation method and application thereof

The lithium slag is converted into efficient zeolite through alkali grinding activation method, which solves the problems of lithium slag resource utilization and zeolite stability, and achieves efficient lithium slag resource recovery and gaseous arsenic adsorption effect.

CN119284919AActive Publication Date: 2025-01-10CENT SOUTH UNIV

Patent Information

Application Number
CN202411396392.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-10
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The prior art has failed to obtain a more stable zeolite material through lithium slag preparation, and the crystallinity and yield of zeolite have not been studied, which has led to difficulties in resource utilization of lithium slag.

Method used

Using a method based on alkali mill activation, the lithium slag and alkaline auxiliary materials were ball milled and hydrothermal treatment was carried out in an alkali solution to promote the release and reaction activity of silicon and aluminum elements, thereby preparing a high crystallinity and high yield. Zeolite.

Benefits of technology

It has achieved efficient zeolites obtained through lithium slag preparation, with higher sulfur resistance and high temperature adsorption resistance, providing a new way to resource treatment of lithium slag and reducing gaseous arsenic emissions in nonferrous smelting enterprises.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284919A_ABST
    Figure CN119284919A_ABST
Patent Text Reader

Abstract

The invention provides analcime based on alkali grinding activation as well as a preparation method and application of the analcime. The preparation method of analcime comprises the following steps: S1, providing lithium slag; s2, ball-milling the solid material and water together to obtain a ball-milled product; the solid material comprises the lithium slag and an alkaline auxiliary material, and the alkaline auxiliary material comprises one or more of sodium hydroxide and potassium hydroxide; s3, mixing the ball-milled product with an alkaline solution to obtain a to-be-treated solution; performing hydro-thermal treatment on the to-be-treated liquid to obtain reaction liquid; and S4, carrying out solid-liquid separation on the reaction liquid to obtain a solid isolate containing analcime. The analcime with high crystallinity and high yield can be obtained, a new way is provided for preparation of the analcime, and a new way is also provided for resourceful treatment of the lithium slag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of treated analcime, in particular to analcime activated based on alkali grinding and a preparation method and application thereof. Background Art

[0002] The production process of lithium carbonate includes the traditional limestone roasting method and the widely used sulfuric acid method, sulfate method and chloride roasting method. In addition, new technologies such as alkali dissolution method, pressure cooking method and composite salt roasting have been developed. After lithium ore is batched, roasted at high temperature and leached, lithium is extracted into the solution; however, the lithium leaching slag (hereinafter referred to as lithium slag) is piled up in the factory. Lithium slag is an industrial siliceous aluminum waste slag. For every ton of Li2CO3 produced, about 20-30 tons of lithium slag are produced; therefore, lithium slag is a large amount of solid waste that is inevitably produced in the lithium extraction process, and faces problems such as large stockpiles and difficulties in resource utilization.

[0003] Analcime is a common feldspar-like mineral belonging to the zeolite family with special structure and properties. Analcime has ion exchange, catalytic properties, thermal stability and acid resistance, and is widely used in building materials, environmental protection, daily light industry, petrochemical industry and other fields. However, although lithium slag has been treated in existing studies, analcime products have not been obtained.

[0004] The Chinese invention patent application with publication number CN117643861A (the applicant's previous case) discloses a sulfur-resistant and high-temperature-resistant gaseous arsenic adsorption material and its preparation method and application. Although the gaseous arsenic adsorption material is prepared by mechanically ball-milling and activating lithium slag, which has application value, it does not obtain analcime materials with more stable structure through lithium slag, nor does it study the crystallinity and yield of analcime.

[0005] In view of this, it is necessary to provide analcime based on alkali grinding activation and a preparation method and application thereof, so as to solve or at least alleviate the technical problem of how to prepare analcime from lithium slag. Summary of the invention

[0006] The main purpose of the present invention is to provide analcime activated by alkali grinding and a preparation method and application thereof, aiming to solve the above-mentioned technical problem of how to prepare analcime from lithium slag.

[0007] To achieve the above object, the present invention provides a method for preparing analcime based on alkali grinding activation, comprising the steps of:

[0008] S1, providing lithium slag; the lithium slag contains Li element, Si element, Al element, Na element, K element, F element and Ca element;

[0009] S2, ball-milling the solid material and water to obtain a ball-milled product;

[0010] The solid material includes the lithium slag and the alkaline auxiliary material, the mass percentage of the water and the solid material is 10-50%; the mass ratio of the alkaline auxiliary material to the lithium slag is 1:2-10; the alkaline auxiliary material includes one or more of sodium hydroxide and potassium hydroxide; the ball milling time is not less than 100 minutes;

[0011] S3, mixing the ball-milled product and an alkaline solution to obtain a liquid to be treated; and subjecting the liquid to be treated to a hydrothermal treatment to obtain a reaction liquid;

[0012] The alkaline solution contains alkaline substances, and the alkaline substances include one or more of sodium hydroxide and potassium hydroxide; the temperature of the hydrothermal treatment is 130-210° C., and the duration of the hydrothermal treatment is 40-180 min;

[0013] S4, performing solid-liquid separation on the reaction liquid to obtain a solid separation; the solid separation contains analcime.

[0014] Furthermore, the mass proportion of the Li element in the lithium slag is 0.1-2%, the mass proportion of the Si element in the lithium slag is 10-15%, the mass proportion of the Al element in the lithium slag is 5-12%, the mass proportion of the Na element in the lithium slag is 5-10%, the mass proportion of the K element in the lithium slag is 5-10%, the mass proportion of the F element in the lithium slag is 2-8%, and the mass proportion of the Ca element in the lithium slag is 5-10%.

[0015] Furthermore, the lithium slag contains nepheline, muscovite and orthoclase; and the lithium slag has a framework aluminosilicate structure.

[0016] Furthermore, the alkaline auxiliary material is sodium hydroxide.

[0017] Furthermore, the rotation speed of the ball mill is 300-800 r / min, the duration of the ball mill is 120-175 min, and the ball-to-material mass ratio used in the ball mill is 4-12:1.

[0018] Furthermore, the concentration of the alkaline substance in the alkaline solution is 0.5-4 mol / L; the mass volume ratio of the ball-milled product to the alkaline solution is 1-10 g:40-50 mL.

[0019] Furthermore, the hydrothermal treatment is carried out by microwave hydrothermal treatment; and the microwave hydrothermal treatment is carried out in a microwave hydrothermal reactor.

[0020] The present invention also provides analcime, comprising: preparing the analcime by any of the above-mentioned analcime preparation methods.

[0021] The present invention also provides a use of any of the above-mentioned analcime in arsenic removal or sulfur-resistant arsenic removal.

[0022] Further, the application includes: using the analcime to adsorb arsenic in arsenic-containing flue gas; the arsenic-containing flue gas contains As2O3, or the arsenic-containing flue gas contains As2O3 and SO2;

[0023] The adsorption is carried out at a temperature of 400-900° C. and the adsorption time is 20-90 min;

[0024] When the arsenic-containing flue gas contains As2O3, the concentration of As2O3 in the arsenic-containing flue gas is not higher than 1 mg / L;

[0025] When the arsenic-containing flue gas contains As2O3 and SO2, the concentration of As2O3 in the arsenic-containing flue gas is not higher than 1 mg / L, and the volume proportion of SO2 in the arsenic-containing flue gas is not higher than 15%.

[0026] Compared with the prior art, the present invention has at least the following advantages:

[0027] The present invention can prepare analcime from lithium slag; the present invention ball-mills lithium slag, alkaline auxiliary materials and water together, and uses OH- in the alkaline auxiliary materials to attack the aluminosilicate skeleton during ball milling, which can promote the release of silicon and aluminum elements and increase the reaction activity of lithium slag; the present invention ball-mills lithium slag with specific alkaline auxiliary materials in a wet environment, and then hydrothermally synthesizes the ball-milled product in a specific alkaline solution to obtain analcime with higher crystallinity and yield; therefore, the present invention provides a new way for the preparation of analcime, and also provides a new way for the resource treatment of lithium slag. The analcime in the present invention not only has a high sulfur resistance and arsenic removal performance, but more importantly, the present invention also has a higher tolerance temperature and has a higher adsorption capacity for arsenic at around 800°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0029] Figure 1 The XRD diagram of the lithium slag in the analysis example 1 of the present invention;

[0030] Figure 2 The activity index diagram of lithium slag after ball milling at different ball milling speeds in Example 1 of the present invention;

[0031] Figure 3 The activity index diagram of lithium slag after ball milling at different ball milling times in Example 2 of the present invention;

[0032] Figure 4 The activity index diagram of lithium slag after ball milling at different ball-to-material ratios in Example 3 of the present invention;

[0033] Figure 5 The activity index diagram of lithium slag after ball milling under different auxiliary material ratios (different proportions) in Example 4 of the present invention;

[0034] Figure 6 The activity index diagram of lithium slag after ball milling at different moisture contents (different mass fractions) in Example 5 of the present invention;

[0035] Figure 7 : is the XRD diagram of the lithium slag and the prepared product in Example 6 of the present invention; in the figure, the original slag is lithium slag, and the product is the prepared product in Example 6;

[0036] Figure 8 This is a SEM image of the product (analcime) prepared in Example 6 of the present invention;

[0037] Fig. 9 This is a diagram showing the effect of the adsorbent adsorbing gaseous arsenic at different adsorption temperatures in Example 7 of the present invention;

[0038] Fig.10 This is a diagram showing the effect of the adsorbent on adsorbing gaseous arsenic at different sulfur dioxide concentrations in Example 8 of the present invention;

[0039] Fig.11 is the XRD pattern of the product prepared in Example 9 of the present invention;

[0040] Fig.12 This is the XRD pattern of the product prepared in Comparative Example 1 of the present invention;

[0041] Fig.13 This is the XRD diagram of the product prepared in Comparative Example 2 of the present invention;

[0042] Fig.14 This is the XRD diagram of the product prepared in Comparative Example 3 of the present invention;

[0043] Fig.15 This is the XRD diagram of the product prepared in Comparative Example 4 of the present invention.

[0044] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0045] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. The embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0047] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any methods, equipment and materials of the prior art similar or equivalent to the methods, equipment and materials described in the embodiments of the present invention can also be used to implement the present invention.

[0048] In the present invention, when calculating the ball-to-material ratio, lithium slag, alkaline auxiliary materials and water are all counted as materials for ball milling. In the embodiments and comparative examples of the present invention, alumina grinding balls are used for ball milling, and the number ratio of alumina grinding balls is large balls (diameter 15mm): medium balls (diameter 10mm): small balls (diameter 5mm) = 15:9:6; in the present invention, further, the number ratio of grinding balls can be large balls (diameter 14-16mm): medium balls (diameter 9-11mm): small balls (diameter 4-6mm) = 14-16:8-10:5-7. The microwave hydrothermal reactor used in the embodiments and comparative examples of the present invention comes from Beijing Xianghu Technology Development Co., Ltd., which is a multifunctional microwave hydrothermal parallel synthesizer, model XH-800SP, and microwave frequency 2450MHz.

[0049] In the present invention, the calculation formula of the activity index of lithium slag after ball milling is: Among them, α represents the activity index of lithium slag after ball milling, m1 represents the active aluminum content in lithium slag after ball milling, and m0 represents the active aluminum content in lithium slag before ball milling.

[0050] In the present invention, the aluminum that can be dissolved after alkali leaching is defined as active aluminum; wherein the alkali leaching steps are as follows:

[0051] Prepare 100mL of 1mol / L sodium hydroxide solution, and pour the solution into a 250mL beaker; place the beaker on a digital constant temperature magnetic stirrer and heat it to 60°C; add 3g of the object to be tested (lithium slag after ball milling or lithium slag before ball milling) into the beaker, and conduct an alkaline leaching experiment with a leaching time of 30min and a stirring speed of 300r / min; after the leaching is completed, filter while hot, acidify the filtrate with concentrated HNO3 to pH <2, and place it in a refrigerator for testing, and then analyze and test the aluminum concentration using ICP-OES; the higher the active aluminum content, the greater the activity of the lithium slag.

[0052] The present invention provides a method for preparing analcime based on alkali grinding activation, comprising the steps of:

[0053] S1, provides lithium slag.

[0054] In the present invention, the lithium slag contains Li element, Si element, Al element, Na element, K element, F element and Ca element; the mass proportion of the Li element in the lithium slag is 0.1-2%, the mass proportion of the Si element in the lithium slag is 10-15%, the mass proportion of the Al element in the lithium slag is 5-12%, the mass proportion of the Na element in the lithium slag is 5-10%, the mass proportion of the K element in the lithium slag is 5-10%, the mass proportion of the F element in the lithium slag is 2-8%, and the mass proportion of the Ca element in the lithium slag is 5-10%.

[0055] In the present invention, the lithium slag contains nepheline, muscovite and orthoclase; the lithium slag has aluminosilicate, especially a framework aluminosilicate structure.

[0056] S2, ball-milling the solid material and water together to obtain a ball-milled product.

[0057] In the present invention, the solid material includes the lithium slag and an alkaline auxiliary material, and the alkaline auxiliary material includes one or more of sodium hydroxide and potassium hydroxide; in order to further improve the crystallinity and yield of analcime, the alkaline auxiliary material is preferably sodium hydroxide.

[0058] In the present invention, the mass percentage of the water and the solid material is 10-50%, preferably 25-35%; the mass ratio of the alkaline auxiliary material to the lithium slag is 1:2-10, preferably 1:4-6 or 1:5; the ball milling time is not less than 100 min, preferably not less than 120 min or 120-175 min, and can further be 120-130 min; the rotation speed of the ball mill is 300-800 r / min, preferably 500-580 r / min or 500-560 r / min; the ball-to-material mass ratio used in the ball mill is 4-12:1, preferably 7-8:1 or 8:1.

[0059] When the ball milling is performed, the present invention performs forward rotation and reverse rotation in sequence, and there is an interval between the forward rotation and the reverse rotation, and between the reverse rotation and the forward rotation; wherein, the set time of each forward rotation is 5-15 minutes (specifically 10 minutes), the set time of each reverse rotation is 5-15 minutes (specifically 10 minutes), and the interval time is set to 3-7 minutes (specifically 5 minutes); when the ball milling time reaches the set time, the ball milling is stopped, and the interval time is included in the ball milling time.

[0060] S3, mixing the ball-milled product and an alkaline solution to obtain a liquid to be treated; and subjecting the liquid to be treated to a hydrothermal treatment (hydrothermal reaction) to obtain a reaction liquid.

[0061] In the present invention, the alkaline solution contains alkaline substances, and the concentration of the alkaline substances in the alkaline solution is 0.5-4 mol / L, preferably 0.8-1.2 mol / L; the alkaline substances include one or more of sodium hydroxide and potassium hydroxide.

[0062] In the present invention, the temperature of the hydrothermal treatment is 130-210°C, preferably 140-160°C; the duration of the hydrothermal treatment is 40-180min, preferably 110-130min; the mass volume ratio of the ball milling product and the alkaline solution is 1-10g:40-50mL, preferably 3g:40-50mL.

[0063] The hydrothermal treatment can be specifically microwave hydrothermal treatment, which is carried out in a microwave hydrothermal reactor. By adopting the microwave hydrothermal treatment, the materials in the reactor can be treated by microwaves during the synthesis stage, so that the crystal nucleation speed is accelerated during the reaction process, and the particle size of the analcime obtained is smaller and the particle size distribution is more uniform.

[0064] S4, performing solid-liquid separation on the reaction liquid to obtain a solid separation (separation residue), wherein the solid separation contains analcime.

[0065] The technical principles of the present invention mainly include:

[0066] First, the lithium slag is activated and its activity is enhanced through mechanical ball milling. Mechanical ball milling uses the rotating drum to make the grinding balls and materials collide, shear and rub continuously in the tank, so as to achieve the effect of material crushing, mixing and enhancing surface activity. The surface of the material is micronized and redispersed, which accelerates the chemical reaction.

[0067] Second, during the ball milling process, the OH in the alkaline auxiliary material is used to -During ball milling, the alkaline auxiliary material attacks the aluminosilicate skeleton, promotes the release of silicon and aluminum elements, and enhances the reaction activity of lithium slag for subsequent microwave hydrothermal synthesis; at the same time, during the ball milling process, the alkaline auxiliary material can also be used as a grinding aid.

[0068] Third, the present invention has specific requirements on the type of alkaline auxiliary materials, mainly due to Na + , K + It can act as an inorganic template during hydrothermal treatment; however, the introduction of Ca 2+ Mg 2+ It will promote volcanic ash reaction and thus inhibit the formation of analcime.

[0069] Fourthly, the present invention has specific requirements for the humidity during the ball milling process, mainly because appropriate moisture can better react with OH - Synergistically destroy the lithium slag structure, thereby promoting the release of Si and Al elements.

[0070] Fifthly, the lithium slag activated by ball milling with alkali is subjected to hydrothermal synthesis. The lithium slag activated by ball milling is dissolved, diffused, monomer reconstructed and condensed in a hydrothermal environment, so that the lithium slag hydrothermal crystallization forms analcime.

[0071] Sixth, the present invention has specific requirements for the alkaline solution used in hydrothermal treatment, mainly because OH - The concentration will affect the crystallization rate of zeolite, so an appropriate concentration should be used; and if other alkaline solutions are introduced into Ca 2+ Mg 2+ , which will promote volcanic ash reaction and thus inhibit the formation of analcime.

[0072] Seventh, the present invention can utilize the F element in lithium slag in situ to play the role of inorganic template during hydrothermal treatment and at the same time 2+ Combined with the formation of CaF2 precipitation, it inhibits the volcanic ash reaction and promotes the formation of analcime.

[0073] The present invention subjects lithium slag to mechanical ball milling activation and hydrothermal synthesis in a specific manner to obtain analcime; analcime is used as an adsorbent to adsorb gaseous arsenic, which can effectively control the emission of gaseous arsenic in non-ferrous smelting enterprises and provide a new resource utilization approach for the disposal of lithium slag in the lithium carbonate industry.

[0074] To this end, the present invention also provides analcime, comprising: preparing the analcime by any of the analcime preparation methods described above.

[0075] The present invention also provides an application of any of the above-mentioned analcime in arsenic removal or sulfur-resistant arsenic removal. That is, the analcime obtained by mechanical ball milling activation and hydrothermal synthesis of lithium slag can be used for adsorption of gaseous arsenic; it not only has a more stable structure, but also has a large adsorption capacity, which can reduce the emission of gaseous arsenic in non-ferrous smelting enterprises.

[0076] As an illustration of the use of analcime in arsenic removal, the application includes: using the analcime to adsorb arsenic in arsenic-containing flue gas; the arsenic-containing flue gas contains As2O3, and other components in the arsenic-containing flue gas may include or be oxygen, argon, and carbon dioxide; the adsorption is carried out at a temperature of 400-900°C (preferably 750-850°C or 750-800°C), and the adsorption time is 20-90min or 30-90min (preferably 25-35min); when the arsenic-containing flue gas contains As2O3, the concentration of As2O3 in the arsenic-containing flue gas is not higher than 1mg / L (preferably 0.5-0.8mg / L).

[0077] As an illustration of the use of analcime in sulfur resistance and arsenic removal, the application includes: using the analcime to adsorb arsenic in arsenic-containing flue gas; the arsenic-containing flue gas contains As2O3 and SO2, and other components in the arsenic-containing flue gas may include or be oxygen, argon, and carbon dioxide; the adsorption is carried out at a temperature of 400-900°C (preferably 750-850°C or 750-800°C), and the adsorption time is 20-90min or 30-90min (preferably 25-35min); when the arsenic-containing flue gas contains As2O3 and SO2, the concentration of As2O3 in the arsenic-containing flue gas is not higher than 1mg / L (preferably 0.5-0.8mg / L), and the volume proportion of SO2 in the arsenic-containing flue gas is not higher than 15% (preferably 4-6% or 5-10%).

[0078] The following are specific examples of the present invention:

[0079] Analysis example 1

[0080] Take the lithium slag stored in a lithium carbonate production company in Jiangxi.

[0081] 1. In this analysis example, the element composition of lithium slag is shown in Table 1. In Table 1, Rb* and Cs* are tested by digestion-ICP, and the remaining elements are tested by XRF.

[0082] Table 1 Element composition of lithium slag (mass %)

[0083]

[0084] 2. In this analysis example, lithium slag contains nepheline, muscovite and orthoclase. For XRD analysis of lithium slag, see Figure 1 As shown; after analysis, the lithium slag has a framework aluminosilicate structure.

[0085] Example 1

[0086] Take the lithium slag in Analysis Example 1 and ball mill them at ball mill speeds of 300, 350, 400, 450, 500, 550, 600, 650, and 700 r / min, respectively, to obtain ball milling products at different ball milling speeds; the ball-to-material ratio used in the ball milling is 6:1, and the ball milling time is 25 min (the ball mill is set to rotate forward for 10 min, interval 5 min, and reverse for 10 min).

[0087] The activity index of the ball-milled product (lithium slag after ball-milling) at different ball-milling speeds was tested; Figure 2 As shown, when the ball milling speed is 550r / min, the activity index of the lithium slag after ball milling reaches 9.1.

[0088] Example 2

[0089] Take the lithium slag in Analysis Example 1, and ball mill them respectively under the conditions of ball milling time of 25, 50, 75, 100, 125, 150, 200, and 250 min (set the ball mill to rotate forward for 10 min, interval 5 min, reverse for 10 min, interval 5 min), and obtain the ball milling products under different ball milling times; the ball-to-material ratio used in the ball milling is 6:1, and the ball milling speed is 550 r / min.

[0090] The activity index of the ball-milled products (lithium slag after ball-milling) at different ball-milling times was tested; Figure 3 As shown in the figure, when the ball milling time reaches 125 min, the activity index of lithium slag after ball milling basically no longer increases, and the activity index reaches 15.2 at this time.

[0091] Example 3

[0092] Take the lithium slag in Analysis Example 1, and ball mill them under the conditions of ball-to-material ratio of 4:1, 6:1, 8:1, and 10:1, respectively. The ball milling products under different ball milling ratios; the ball milling time used is 125min (the ball mill is set to rotate forward for 10min, interval 5min, reverse for 10min, interval 5min), and the ball milling speed is 550r / min.

[0093] The activity index of the ball milling product (lithium slag after ball milling) under different ball-to-material ratios was tested; Figure 4 As shown in the figure, when the ball-to-material ratio is 8:1, the activity index of the lithium slag after ball milling reaches 20; when the ball-to-material ratio is 10:1, the activity index of the lithium slag after ball milling decreases rapidly. It is speculated that there may be too little material, causing part of the lithium slag to adhere to the ball mill and the grinding balls, resulting in systematic errors and making the measured value smaller.

[0094] Example 4

[0095] Take the lithium slag in Analysis Example 1, and ball-mill NaOH and lithium slag together at a mass ratio of 0, 1:5, 2:5, 3:5, 4:5, and 1:1, respectively, to obtain ball-milled products under different ratios (auxiliary material ratios); the ball-to-material ratio used in ball milling is 8:1, the ball milling time is 125 min (the ball mill is set to rotate forward for 10 min, interval 5 min, reverse for 10 min, interval 5 min), and the ball milling speed is 550 r / min.

[0096] The activity index of the ball-milled product (lithium slag after ball-milling) at different ratios (auxiliary material ratios) was tested; Figure 5 As shown in the figure, when the mass ratio of sodium hydroxide to lithium slag is 1:5, the activity index of lithium slag after ball milling reaches 22.4. When the ratio of sodium hydroxide auxiliary material exceeds 1:5, the material becomes compacted and the activity index of lithium slag decreases rapidly.

[0097] Example 5

[0098] Take the lithium slag in Analysis Example 1, use NaOH and lithium slag as solid materials, and ball-mill water and the solid material at mass fractions of 0%, 10%, 20%, 30%, 40%, and 50% (mass percentage of water and solid material) to obtain ball-milled products at different mass fractions; the ball-to-material ratio used in ball milling is 8:1, the mass ratio of NaOH to lithium slag is 1:5, the ball milling time is 125 min (the ball mill is set to rotate forward for 10 min, with an interval of 5 min, and reverse for 10 min, with an interval of 5 min), and the ball milling speed is 550 r / min.

[0099] The activity index of the ball-milled products (lithium slag after ball-milling) with different mass fractions (different water contents) was tested; Figure 6 As shown, when the moisture content (mass percentage of water and solid material) is 30%, the lithium slag activity index reaches 27.5.

[0100] Example 6

[0101] Take the lithium slag in Analysis Example 1, use NaOH and lithium slag as solid materials, and ball-mill water and solid materials together to obtain a ball-milled product (lithium slag after ball milling). In this embodiment, the mass ratio of NaOH to lithium slag is 1:5, the mass percentage of water to solid materials is 30%; the ball-to-material ratio is 8:1, the ball milling time is 125min (the ball mill is set to rotate forward for 10min, interval 5min, reverse for 10min, interval 5min), and the ball milling speed is 550r / min.

[0102] Weigh 3 g of the ball-milled product into a microwave hydrothermal reactor, add 45 mL of 1 mol / L NaOH solution (alkaline solution) and carry out hydrothermal reaction (microwave hydrothermal). The hydrothermal reaction temperature is 150°C and the hydrothermal reaction time is 120 min. After the hydrothermal reaction is completed, a reaction liquid is obtained.

[0103] The reaction solution was centrifuged at 8000 r / min for 10 min at room temperature and vacuum filtered to achieve solid-liquid separation to obtain a separation liquid and separation residue; the separation residue was dried to obtain the prepared product.

[0104] The prepared product was measured by XRD to confirm whether it was analcime. The crystallinity of the prepared product was calculated using jade software. The aluminum content in the separation liquid was measured by ICP, and the analcime yield was calculated by the proportion of aluminum consumed in the reaction in the total aluminum (aluminum in the lithium slag). The aluminum in the separation liquid was defined as unconsumed aluminum, and the aluminum entering the separation slag was defined as aluminum consumed in the reaction. The prepared product was analyzed by SEM to observe its structure.

[0105] like Figure 7 As shown, the prepared product in this example is analcime; the crystallinity is 49.4%; the analcime yield is 42.8%; see Figure 8 As shown, the analcime of this embodiment has a loose and porous structure.

[0106] Example 7

[0107] 0.1 g of the prepared product (analcime) in Example 6 was taken as an adsorbent, and the adsorbent was placed in a gaseous arsenic adsorption system to carry out an arsenic adsorption experiment, and the adsorption time was 30 min.

[0108] In this embodiment, the gaseous arsenic adsorption system is composed of an arsenic hydrogen generator, an adsorption reactor, and an exhaust gas treatment system. The arsenic hydrogen generator produces arsenic hydrogen, which enters the adsorption reactor together with the simulated flue gas; the adsorption reactor is composed of a two-stage reactor, arsenic hydrogen enters the first stage reactor to be oxidized into arsenic trioxide, arsenic trioxide enters the second stage reactor for adsorption reaction, and the exhaust gas is discharged through the exhaust gas treatment system.

[0109] In this embodiment, the atmosphere used for the simulated flue gas is O2 5%, Ar 87%, SO2 5%, CO2 3% by volume, and the flue gas flow rate is 400 mL / min; the concentration of As2O3 in the simulated flue gas is 0.6 mg / L.

[0110] In this embodiment, the above arsenic adsorption experiments were carried out at adsorption temperatures of 400, 500, 600, 700, and 800°C, respectively.

[0111] See also Fig. 9As shown, the prepared product (analcime) in Example 6 can adsorb gaseous arsenic (referring to As2O3) in an amount of 22.4 mg / g at an adsorption temperature of 800°C, and has excellent gaseous arsenic adsorption capacity.

[0112] Example 8

[0113] 0.1 g of the prepared product (analcime) in Example 6 was taken as an adsorbent, and the adsorbent was placed in a gaseous arsenic adsorption system to carry out an arsenic adsorption experiment. The adsorption temperature was 400° C. and the adsorption time was 30 min.

[0114] In this embodiment, the gaseous arsenic adsorption system is composed of an arsenic hydrogen generator, an adsorption reactor, and an exhaust gas treatment system. The arsenic hydrogen generator produces arsenic hydrogen, which enters the adsorption reactor together with the simulated flue gas; the adsorption reactor is composed of a two-stage reactor, arsenic hydrogen enters the first stage reactor to be oxidized into arsenic trioxide, arsenic trioxide enters the second stage reactor for adsorption reaction, and the exhaust gas is discharged through the exhaust gas treatment system.

[0115] In this embodiment, the above arsenic adsorption experiment is carried out on different simulated flue gases; the compositions of the simulated flue gases are respectively:

[0116] In terms of volume percentage, the atmosphere used for the simulated flue gas (corresponding to 0%) is O2 5%, Ar 92%, SO20%, CO23%, and the flue gas flow rate is 400mL / min; the concentration of As2O3 in the simulated flue gas is 0.6mg / L.

[0117] In terms of volume percentage, the atmosphere used for the simulated flue gas (corresponding to 5%) is O2 5%, Ar 87%, SO25%, CO23%, and the flue gas flow rate is 400mL / min; the concentration of As2O3 in the simulated flue gas is 0.6mg / L.

[0118] In terms of volume percentage, the atmosphere used for the simulated flue gas (corresponding to 10%) is O2 5%, Ar 82%, SO2 10%, CO2 3%, and the flue gas flow rate is 400mL / min; the concentration of As2O3 in the simulated flue gas is 0.6mg / L.

[0119] See also Fig.10 As shown, when the SO2 concentration is 5%, the gaseous arsenic (referring to As2O3) adsorption capacity of the product (analcime) prepared in Example 6 can reach 16.78 mg / g, which has excellent gaseous arsenic adsorption capacity.

[0120] Example 9

[0121] 1. Obtaining the prepared product:

[0122] When obtaining the prepared product, compared with Example 6, the NaOH in the solid material of this example is adjusted to KOH, and other conditions remain unchanged.

[0123] In this embodiment, see Fig.11 As shown, the prepared product is analcime with a crystallinity of 43.2% and analcime yield of 38.7%.

[0124] 2. Arsenic adsorption experiment:

[0125] When conducting the arsenic adsorption experiment, compared with Example 7, the adsorbent in this example is adjusted to the prepared product in this example, and the adsorption temperature is limited to 800° C., and other conditions remain unchanged.

[0126] In this embodiment, the adsorption amount of gaseous arsenic (referring to As2O3) by the adsorbent is 21.8 mg / g.

[0127] Comparative Example 1

[0128] 1. Obtaining the prepared product:

[0129] When obtaining the prepared product, compared with Example 6, the alkaline solution used in the hydrothermal process of this comparative example was adjusted to a hydrochloric acid solution, and other conditions remained unchanged.

[0130] In this comparative example, see Fig.12 As shown, no analcime was produced in the product.

[0131] 2. Arsenic adsorption experiment:

[0132] When conducting the arsenic adsorption experiment, compared with Example 7, the adsorbent in this comparative example was adjusted to the prepared product in this comparative example, and the adsorption temperature was limited to 800° C., while other conditions remained unchanged.

[0133] In this comparative example, the adsorption amount of gaseous arsenic (referred to as As2O3) by the adsorbent is 1.72 mg / g.

[0134] Comparative Example 2

[0135] 1. Obtaining the prepared product:

[0136] When obtaining the prepared product, compared with Example 6, this comparative example directly ball-milled NaOH and lithium slag as solid materials (without adding water), and other conditions remained unchanged.

[0137] In this comparative example, see Fig.13 As shown, the prepared product is analcime with a crystallinity of 35.3% and analcime yield of 32.0%.

[0138] 2. Arsenic adsorption experiment:

[0139] When conducting the arsenic adsorption experiment, compared with Example 7, the adsorbent in this comparative example was adjusted to the prepared product in this comparative example, and the adsorption temperature was limited to 800° C., while other conditions remained unchanged.

[0140] In this comparative example, the adsorption amount of gaseous arsenic (referred to as As2O3) by the adsorbent is 20.85 mg / g.

[0141] Comparative Example 3

[0142] 1. Obtaining the prepared product:

[0143] When obtaining the prepared product, compared with Example 6, the lithium slag in this comparative example is directly ball-milled (without adding NaOH and water), and other conditions remain unchanged.

[0144] In this comparative example, see Fig.14 As shown, analcime was generated in the prepared product, but the crystallinity was only 13.1% and the yield was 8.1%.

[0145] 2. Arsenic adsorption experiment:

[0146] When conducting the arsenic adsorption experiment, compared with Example 7, the adsorbent in this comparative example was adjusted to the prepared product in this comparative example, and the adsorption temperature was limited to 800° C., while other conditions remained unchanged.

[0147] In this comparative example, the adsorption amount of gaseous arsenic (referred to as As2O3) by the adsorbent is 13.69 mg / g.

[0148] Comparative Example 4

[0149] 1. Obtaining the prepared product:

[0150] When obtaining the prepared product, compared with Example 6, this comparative example directly uses the ball milled product as the prepared product (without performing a hydrothermal process), and other conditions remain unchanged.

[0151] In this comparative example, see Fig.15 As shown, the ball milling product is an amorphous aluminosilicate.

[0152] 2. Arsenic adsorption experiment:

[0153] When conducting the arsenic adsorption experiment, compared with Example 7, the adsorbent in this comparative example was adjusted to the prepared product in this comparative example, and the adsorption temperature was limited to 800° C., while other conditions remained unchanged.

[0154] In this comparative example, the adsorption amount of gaseous arsenic (referred to as As2O3) by the adsorbent is 10.13 mg / g.

[0155] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing analcime based on alkali grinding activation, characterized in that: Includes steps: S1, providing lithium slag; the lithium slag contains Li element, Si element, Al element, Na element, K element, F element and Ca element; S2, ball-milling the solid material and water to obtain a ball-milled product; The solid material includes the lithium slag and the alkaline auxiliary material, the mass percentage of the water and the solid material is 10-50%; the mass ratio of the alkaline auxiliary material to the lithium slag is 1:2-10; the alkaline auxiliary material includes one or more of sodium hydroxide and potassium hydroxide; the ball milling time is not less than 100 minutes; S3, mixing the ball-milled product and an alkaline solution to obtain a liquid to be treated; and subjecting the liquid to be treated to a hydrothermal treatment to obtain a reaction liquid; The alkaline solution contains an alkaline substance, and the alkaline substance includes one or more of sodium hydroxide and potassium hydroxide; the temperature of the hydrothermal treatment is 130-210° C., and the duration of the hydrothermal treatment is 40-180 min; S4, performing solid-liquid separation on the reaction liquid to obtain a solid separation; the solid separation contains analcime.

2. The method for preparing analcime according to claim 1, characterized in that: The mass proportion of the Li element in the lithium slag is 0.1-2%, the mass proportion of the Si element in the lithium slag is 10-15%, the mass proportion of the Al element in the lithium slag is 5-12%, the mass proportion of the Na element in the lithium slag is 5-10%, the mass proportion of the K element in the lithium slag is 5-10%, the mass proportion of the F element in the lithium slag is 2-8%, and the mass proportion of the Ca element in the lithium slag is 5-10%.

3. The method for preparing analcime according to claim 1, characterized in that: The lithium slag contains nepheline, muscovite and orthoclase; the lithium slag has a framework aluminosilicate structure.

4. The method for preparing analcime according to claim 1, characterized in that: The alkaline auxiliary material is sodium hydroxide.

5. The method for preparing analcime according to claim 1, characterized in that: The rotation speed of the ball mill is 300-800 r / min, the duration of the ball mill is 120-175 min, and the ball-to-material mass ratio used in the ball mill is 4-12:

1.

6. The method for preparing analcime according to claim 1, characterized in that: The concentration of the alkaline substance in the alkaline solution is 0.5-4 mol / L; the mass volume ratio of the ball-milled product to the alkaline solution is 1-10 g:40-50 mL.

7. The method for preparing analcime according to claim 1, characterized in that: The hydrothermal treatment is carried out in a microwave hydrothermal reactor.

8. Analcime, characterized in that: include: The analcime is prepared by the method for preparing analcime according to any one of claims 1 to 7.

9. Use of the analcime as claimed in claim 8 in arsenic removal or sulfur-resistant arsenic removal.

10. The use according to claim 9, characterized in that: The application includes: using the analcime to adsorb arsenic in arsenic-containing flue gas; the arsenic-containing flue gas contains As2O3, or the arsenic-containing flue gas contains As2O3 and SO2; The adsorption is carried out at a temperature of 400-900° C. and the adsorption time is 20-90 min; When the arsenic-containing flue gas contains As2O3, the concentration of As2O3 in the arsenic-containing flue gas is not higher than 1 mg / L; When the arsenic-containing flue gas contains As2O3 and SO2, the concentration of As2O3 in the arsenic-containing flue gas is not higher than 1 mg / L, and the volume proportion of SO2 in the arsenic-containing flue gas is not higher than 15%.

Citation Information

Patent Citations

  • X zeolite molecular sieve and preparation method thereof

    CN110950351A

  • Sulfur-resistant and high-temperature-resistant gaseous arsenic adsorption material as well as preparation method and application thereof

    CN117643861A

  • Zeolite and preparation method therefor

    US20220033269A1

Cited By

  • Method for preparing analcime from lithium slag

    CN119503834A

  • Method for preparing analcime using lithium slag

    CN119503834B

  • Method for preparing low heavy metal slow-release potassium fertilizer by using lithium smelting slag

    CN122958225A